2023
DOI: 10.1002/advs.202206144
|View full text |Cite
|
Sign up to set email alerts
|

Reprogramming of Mitochondrial Respiratory Chain Complex by Targeting SIRT3‐COX4I2 Axis Attenuates Osteoarthritis Progression

Abstract: Mitochondrial homeostasis is of great importance for cartilage integrity and associated with the progression of osteoarthritis (OA); however, the underlying mechanisms are unknown. This study aims to investigate the role of mitochondrial deacetylation reaction and investigate the mechanistic relationship OA development. Silent mating type information regulation 2 homolog 3 (SIRT3) expression has a negative correlation with the severity of OA in both human arthritic cartilage and mice inflammatory chondrocytes.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 17 publications
(12 citation statements)
references
References 67 publications
0
6
0
Order By: Relevance
“…They also produce various cytokines, like arginase (Arg), IL-10, IL-1 receptor antagonist (IL-1ra), and the type II IL-1 decoy receptor. 14 , 30 , 31 Since investigations have shown that synovial macrophage polarization is closely associated with OA, 5 , 32 , 33 precise therapies for macrophage to decrease synovitis and attenuate OA progression need to be clearly proposed.…”
Section: Discussionmentioning
confidence: 99%
“…They also produce various cytokines, like arginase (Arg), IL-10, IL-1 receptor antagonist (IL-1ra), and the type II IL-1 decoy receptor. 14 , 30 , 31 Since investigations have shown that synovial macrophage polarization is closely associated with OA, 5 , 32 , 33 precise therapies for macrophage to decrease synovitis and attenuate OA progression need to be clearly proposed.…”
Section: Discussionmentioning
confidence: 99%
“…They also produce various cytokines, like arginase (Arg), IL-10, IL-1 receptor antagonist (IL-1ra), and the type II IL-1 decoy receptor. [30][31][32] Since investigations have shown that synovial macrophage polarization is closely associated with OA, [33][34][35] precise therapies for macrophage to decrease synovitis and attenuate OA progression need to be clearly proposed.…”
Section: Discussionmentioning
confidence: 99%
“…82 It was found that SIRT3 plays a role in maintaining mitochondrial homeostasis by deacetylating cytochrome c oxidase subunit 4 isoform 2 (COX4I2). 83 Additionally, SIRT6 was found to deacetylate STAT5, which inactivates IL-15/JAK3/STAT5. 84 These actions serve as negative regulators of the inflammatory response and RANKL-induced osteolysis.…”
Section: Molecular Modification Of Osteolysismentioning
confidence: 99%